Designing Etnopedagogy: The Philosophy of Tri Hita Karana as The Foundation of Educational Values - Metera, I Gde Made; Sugiarka, I Gede; Sukrayasa, I Wayan; Widyastuti, Ni Putu; Rumbay, Christar Arstilo (Advances In Social Humanities Research, 2025)
Education based on local wisdom plays an essential role in shaping students' character in alignment with cultural values. The Tri Hita Karana philosophy, a fundamental concept in Balinese society, emphasizes the balance of relationships between humans and God (Parahyangan), humans and their fellow beings (Pawongan), and humans and nature (Palemahan). This research aims to design and develop an ethnopedagogical concept based on Tri Hita Karana as the foundation of educational values. The research method used is qualitative descriptive with a constructive approach, involving literature studies, interviews with cultural figures and educators, as well as observations of educational practices in Bali. The findings indicate that the implementation of Tri Hita Karana values in education can be carried out through three main approaches: developing a curriculum based on local wisdom, integrating Tri Hita Karana values into existing subjects, and implementing educational programs oriented toward social, environmental, and spiritual balance. By incorporating the Tri Hita Karana philosophy into the education system, students not only acquire academic knowledge but also develop an awareness of the importance of maintaining harmony in life. In conclusion, ethnopedagogy based on Tri Hita Karana has great potential in strengthening character education and shaping a generation with balanced intellectual, social, and spiritual intelligence.